Isolation, Characterization and Comparative Study of Lactobacillus Sp. using FTIR Based Statistical Analysis - Madathanapalli Shruti; Lasya Gona, C. Ramalingam*, Yashita Uttamchandani (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> There are different types of Lactobacilli found in milk. Lactobacilli have antimicrobial activity. In this experiment we try to characterize the lactobacilli found in different sources. For characterization we have used various lactobacilli sources such as Benny Buttermilk, Aavin curd and Ranipet curd, all of which are locally available. Lactobacillus strain Lactobacillus MTCC 2997 and probiotic drinks Bifilac and Darolac were also used as lactobacilli sources. Gram staining and other biochemical tests like Voges Proskauer Test, Methyl Red Test, Citrate Utilization Test, Catalase Test, as per their standard procedures were performed. Fourier-transformation infrared spectroscopy (FTIR) was applied to characterizeÂ Lactobacillus from different sources at the genus and species level. Similarity matrices, cluster analysis and correlation plots were made to compare how similar 2 strains of isolated Lactobacillus sp. are over the entire FTIR range of wavenumbers are. The scatter plot and similarity matrix shows strong positive correlation of 0.966 between Lactobacillus sp. isolated from Benny buttermilk and that of Ranipet curd hence these two strains have a very similar lactic acid production rate. ANOVA tables and curve estimation was done to compare each isolated strain with MTCC 2997. During this analysis it was obtained that, Lactobacillus MTCC 2997 and Lactobacillus sp. isolated from Bifilac were 94.6% similar. When Hierarchical Cluster Analysis was performed, the dendogram also depicted that Lactobacillus MTCC 2997 and Lactobacillus sp. isolated from Bifilac were closely related .The importance of this method is that it states the amount of similarity between the organisms using statistical analysis. Based on this similarity percentage, measured in terms of Pearson correlation, we can predict the strain type, differentiate up to the sub species level, which was not possible with biochemical characterization.